Nomenclature and Classification of Odontogenic Tumors — Part I: Historical Review. (December 2014) - Soukup, Jason W.; Bell, Cynthia M.
Odontogenic tumor nomenclature and classification is frustrating for both physicians and veterinarians. There has been and continues to be an evolution of the terms and taxonomy used in veterinary and human literature. In this historical review, we aim to provide veterinarians a fundamental basis for understanding how the etymology for odontogenic tumors has evolved over the past two centuries.